Dietary flax oil rich in α-linolenic acid reduces renal disease and oxylipin abnormalities, including formation of docosahexaenoic acid derived oxylipins in the CD1-pcy/pcy mouse model of nephronophthisis. (March 2015) - Yamaguchi, Tamio; Devassy, Jessay G.; Gabbs, Melissa; Ravandi, Amir; Nagao, Shizuko; Aukema, Harold M.
Abstract: The CD1- pcy/pcy mouse model of nephronophthisis displays reduced renal docosahexaenoic acid (DHA) levels and alterations in renal cyclooxygenase and lipoxygenase oxylipins derived from n -6 fatty acids. Since dietary flax oil ameliorates disease progression, its effect on renal fatty acids and oxylipins was examined. Sixteen weeks of feeding resulted in reduced disease progression and enrichment of renal phospholipid α-linolenic acid (ALA) and eicosapentaenoic acid, reduction in arachidonic acid (AA), but no change in linoleic acid (LA) or DHA. In diseased kidneys, flax oil feeding mitigated the elevated levels of renal cyclooxygenase derived oxylipins formed from AA and the lowered lipoxygenase and cytochrome P450 derived oxylipins formed from ALA and DHA. Increased DHA oxylipins occurred with flax feeding despite not altering DHA levels. Dietary flax oil may therefore reduce disease progression via mitigation of oxylipin abnormalities. This study also provides evidence of in vivo ALA conversion to DHA in amounts necessary to restore DHA oxylipin levels.